The Effect of the Covid-19 Pandemic on the Innovation Process of Small and Medium-sized Regional Firms - Hidenori Shigeno; Taisuke Matsuzaki; Yasushi Ueki; Masatsugu Tsuji (International Telecommunications Society (ITS), 2023)
The objective of this study is to analyze how the innovation process has been affected by Covid-19 pandemic by focusing on SMEs. The RQs are: RQ1: Whether there is a difference in the innovation of SMEs between before and during Covid-19 RQ2: If any, how Covid-19 affects the innovation process This study is based on two surveys in February 2014 and 2022 to the same 1324 SMEs and 87 which responded to both surveys are employed for analysis. Measures include (i) the ratio of R&D investment to sales, (ii) open innovation, (iii) sources of ideas, (iv) problem solving ability, (v) human resource development, (vi) business development strategies. In the second questionnaire, the level of the effect of Covid-19 on variables are asked for the five Likert scale. The method used in this study is PSM-DID, which is the combination DID and PSM and to cope with biases such as sample selection and time trend. For the construction of the model, in-depth field surveys were conducted, which leads to hypothesis such that face-to-face communications were impeded between partners of transactions by the COVID-19 pandemic. This hypothesis and RQs are demonstrated by PSM-DID.
Keywords: 330; PSM-DID; measures of innovation; open innovation; R&D; open innovation; face-to-face communications